Gene Expression Changes Induced by Trypanosoma cruzi Shed Microvesicles in Mammalian Host Cells: Relevance of tRNA-Derived Halves. (9th April 2014) - Garcia-Silva, Maria R.; Cabrera-Cabrera, Florencia; Cura das Neves, Roberta Ferreira; Souto-Padrón, Thaís; de Souza, Wanderley; Cayota, Alfonso
Abstract : At present, noncoding small RNAs are recognized as key players in novel forms of posttranscriptional gene regulation in most eukaryotes. However, canonical small RNA pathways seem to be lost or excessively simplified in some unicellular organisms including Trypanosoma cruzi which lack functional RNAi pathways. Recently, we reported the presence of alternate small RNA pathways in T. cruzi mainly represented by homogeneous populations of tRNA- and rRNA-derived small RNAs, which are secreted to the extracellular medium included in extracellular vesicles. Extracellular vesicle cargo could be delivered to other parasites and to mammalian susceptible cells promoting metacyclogenesis and conferring susceptibility to infection, respectively. Here we analyzed the changes in gene expression of host HeLa cells induced by extracellular vesicles from T. cruzi . As assessed by microarray assays a large set of genes in HeLa cells were differentially expressed upon incorporation of T. cruzi -derived extracellular vesicles. The elicited response modified mainly host cell cytoskeleton, extracellular matrix, and immune responses pathways. Some genes were also modified by the most abundant tRNA-derived small RNAs included in extracellular vesicles. These data suggest that microvesicles secreted by T. cruzi could be relevant players in early events of the T. cruzi host cell interplay.